myTrustedCloud: Trusted Cloud Infrastructure for Security-critical Computation and Data Managment - Wallom, David; Turilli, Matteo; Martin, Andrew; Raun, Anbang; Taylor, Gareth; Hargreaves, Nigel; McMoran, Alan (My University, 2012)
Cloud Computing provides an optimal infrastructure to utilise and share both computational and data resources whilst allowing a pay-per-use model, useful to cost-effectively manage hardware investment or to maximise its utilisation. Cloud Computing also offers transitory access to scalable amounts of computational resources, something that is particularly important due to the time and financial constraints of many user communities. The growing number of communities that are adopting large public cloud resources such as Amazon Web Services [1] or Microsoft Azure [2] proves the success and hence usefulness of the Cloud Computing paradigm. Nonetheless, the typical use cases for public clouds involve non-business critical applications, particularly where issues around security of utilization of applications or deposited data within shared public services are binding requisites. In this paper, a use case is presented illustrating how the integration of Trusted Computing technologies into an available cloud infrastructure -- Eucalyptus -- allows the security-critical energy industry to exploit the flexibility and potential economical benefits of the Cloud Computing paradigm for their business-critical applications.
Keywords: 33 Ciencias Tecnológicas::3306 Ingeniería y tecnología eléctricas; ODS 9 - Industria, innovación e infraestructura; Cloud computing; Data models; Computational modeling; Kernel; Servers; Load modeling